Cortical activity associated with focal muscle vibration applied directly to the affected forearm flexor muscle in post-stroke patients: an fNIRS study - Shen, Xianshan; Yu, Yang; Xiao, Han; Ji, Leilei; Wu, Jianxian (Frontiers in Neuroscience, 2023)
This study used fNIRS to identify cortical activity changes caused by focal muscle vibration FMV in hemiplegic stroke patients' affected forearm flexor muscles. The study aimed to correlate these changes with clinical characteristics, expanding the understanding of potential neurophysiological mechanisms. Methods: Our study involved 22 stroke patients with right hemiplegia who were admitted to our rehabilitation ward, and we collected fNIRS data using a block-design paradigm. The collected data were analyzed using the NirSpark software to determine the mean Oxyhemoglobin (Hbo) concentrations for each cortical region of interest (ROI). The stimulation task was FMV directly applied to the affected belly of the flexor carpi radialis muscle (FCR). Hbo was measured in six regions of interest (ROIs) in the cerebral cortex, which included the bilateral prefrontal cortex (PFC), sensorimotor cortex (SMC), and occipital cortex (OC). The clinical characteristics of the patients were assessed concurrently, including Lovett's 6-level muscle strength assessment, clinical muscle tone assessment, the upper extremity function items of the Fugl-Meyer Assessment (FMA-UE), Bruunstrom staging scale (BRS), and Modified Barthel index (MBI). Results: Statistical analysis revealed that, except for right OC, there were statistically significant differences between the mean Hbo in the task state and rest state for bilateral SMC, PFC, and left OC. A positive correlation was observed between the muscle strength of the affected wrist flexor group and the change values of Hbo (Hbo-CV) or the beta values in the left SMC, PFC, and OC. However, no statistical correlation was found between muscle strength and Hbo-CV or beta values in the right SMC, PFC, and OC. The BRS exhibited a positive correlation with the Hbo-CV or beta values in the left SMC and PFC. In contrast, no statistical correlation was observed in the right SMC, PFC, and bilateral OC. No significant correlation was found between the muscle tone of the affected wrist flexor group, FMA-UE, MBI, and Hbo-CV or beta values of cortical ROIs. The results of this study provide neurophysiological theoretical support for the expanded clinical application of FMV.